Belgian children's letters to President Woodrow Wilson
Letters (1915 February-March) of Belgian school children addressed to President Wilson, expressing gratitude for American relief during World War I. Many of the letters are decorated with art work and calligraphy and some include photographs or ribbons.
Collection material in Flemish and French, with several translated into English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Wilson, Woodrow, -- 1856-1924 -- Correspondence; School children -- Belgium -- Correspondence; World War, 1914-1918 -- Children -- Belgium; World War, 1914-1918 -- Civilian relief -- Belgium